Pharmacological Basis for Use of a Novel Compound in Hyperuricemia: Anti-Hyperuricemic and Anti-Inflammatory Effects - Zhao, Lei; Li, Yihang; Yao, Dahong; Sun, Ran; Liu, Shifang; Chen, Xi; Lin, Congcong; Huang, Jian; Wang, Jinhui; Li, Guang (Frontiers in Pharmacology, 2021)
Background: The prevalence of hyperuricemia (HUA) can be considered high worldwide. Hyperuricemia occurs due to decreased excretion of uric acid, increased synthesis of uric acid or a combination of both mechanisms. There is growing evidence that hyperuricemia is associated with a decline of renal function. Purpose: This study is aimed at investigating the effects of the novel compound to lower the serum uric acid (UA) level and alleviate high UA-induced renal inflammation in hyperuricemic mice. Methods: Potassium oxonate induced hyperuricemia mice model was used to evaluate the effects of the novel compound. Serum uric acid, creatinine (Cr), blood urea nitrogen (BUN), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and xanthine oxidase (XOD) levels were measured. Hematoxylin-eosin staining was applied to observe pathological changes. The mRNA expression levels were tested by qRT-PCR. The protein expression levels of inflammatory cytokines and uric acid transporters were determined by Western blot. In parallel, human proximal renal tubular epithelial cells (HK-2) derived from normal kidney was used to further validate the anti-inflammatory effect in vitro. Results: FxUD administration significantly decreased serum uric acid levels, restored the kidney function parameters, and improved the renal pathological injury. Meanwhile, treatment with FxUD effectively inhibited serum and liver XOD levels. Reversed expression alterations of renal inflammatory cytokines (IL-1β, TNF-α, IL-6 and MCP-1) and urate transporter 1 (URAT1), glucose transporter 9 (GLUT9) were observed in hyperuricemic mice. Western blot results illustrated FxUD down-regulated protein levels of inflammasome components. Further studies showed that FxUD inhibited PO-induced the activation of NF-κB signaling pathway in the kidney of hyperuricemic mice. In parallel, The anti-inflammatory effect of the compound was also confirmed in HK-2. Conclusion: Our study revealed that FxUD exhibited the anti-hyperuricemic and anti-inflammatory effects through regulating hepatic XOD activity and renal urate reabsorption transporters, and suppressing NF-κB/NLRP3 pathway in hyperuricemia. The results provided the evidence that FxUD may be potential for the treatment of hyperuricemia with kidney inflammation.